La escala de Likert en la valoración de los conocimientos y las actitudes de los profesionales de enfermería en el cuidado de la salud. Antioquia, 2003 (2005)
ABSTRACT: The objective of this paper is describe the process of validation of scale type Likert used for measure the knowledge and attitudes that nursing professionals of Antioquia (Colombia) had in the communities health care in the 2003. At this meaning an instrument was elaborated using a Likert scale, with closed questions, referred to the areas of communities care, health promotion, prevention of disease, human development, social participation and education for health, intention of the thought about questions was guided to value the opinions, enjoyments, the satisfaction and the knowledge about mentioned areas. Their application explored the tendencies and the variances the answers had about attitude toward the health care, either positive or negative. The more notable result was a positive direction in attitude (59%) in the Likert’s scale at the Nursing professionals toward their practice in the human communities care.